First report on identification of Salmonella Abortusovis from ovine abortion cases in Kazakhstan - Mussayeva, Assiya; Abay, Zhandos; Dossanova, Aigul; Nissanova, Raikhan; Yerishov, Merey; Yegorova, Natalya; Arysbekova, Altynay; Yussupov, Malik; Akshalova, Perizat; Kirpichenko, Vladimir; Abduraimov, Yergali; Zakarya, Kunsulu; et al. (Frontiers in Veterinary Science, 2026)
Salmonella enterica subsp. enterica serovar Abortusovis is a host-adapted ovine pathogen responsible for late-term abortions and significant economic losses in sheep farming. Despite its recognized importance, up-to-date epizootic data on the global distribution and genetic diversity of this serovar remain notably scarce. In this brief communication, we report the isolation and 16S rRNA-based identification of six S. Abortusovis isolates recovered from five aborted lambs during a single outbreak in the Karaganda region. Bacterial isolation was performed using non-selective enrichment on meat-peptone broth and plating on meat-peptone agar, followed by 16S rRNA gene amplification yielding ~1,100 bp PCR products. Six isolates were identified by 16S rRNA sequencing, showing 99% identity with S. enterica serovars Choleraesuis and Paratyphi C. Phylogenetic analysis confirmed their taxonomic position. Phylogenetic analysis using the Maximum Likelihood method (MEGA 11) placed the isolates within a clade including serovars Choleraesuis and Paratyphi C, suggesting close evolutionary proximity. Detailed analysis of electropherograms confirmed the purity of cultures and excluded contamination. Given the lack of recent molecular surveillance data on S. Abortusovis from many regions, including Central Asia, our findings fill an important gap and provide reference material for comparative studies. Further molecular monitoring is needed to support robust diagnostics, trace transmission pathways, and inform regional control strategies against ovine salmonellosis.